2015
DOI: 10.1136/archdischild-2015-308843
|View full text |Cite
|
Sign up to set email alerts
|

Growth restriction and gender influence cerebral oxygenation in preterm neonates

Abstract: Growth restriction and gender influence cerebral oxygenation and oxygen extraction in preterm neonates throughout the first 3 days of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
7
31
1
Order By: Relevance
“…In addition, small for gestational age newborns had comparatively higher rSO 2 values than appropriate for gestational age peers. 53 For example, the 10th, 50th, and 90th percentile for rSO 2 in the first 12 hours of life in preterm infants born at 24 to 25 weeks' gestation was 52%, 62%, and 72%, respectively, whereas in preterm infants born at 30 to 31 weeks' gestation, it was 58%, 68%, and 78%, respectively.…”
Section: Individualization Of Oxygen Exposurementioning
confidence: 98%
“…In addition, small for gestational age newborns had comparatively higher rSO 2 values than appropriate for gestational age peers. 53 For example, the 10th, 50th, and 90th percentile for rSO 2 in the first 12 hours of life in preterm infants born at 24 to 25 weeks' gestation was 52%, 62%, and 72%, respectively, whereas in preterm infants born at 30 to 31 weeks' gestation, it was 58%, 68%, and 78%, respectively.…”
Section: Individualization Of Oxygen Exposurementioning
confidence: 98%
“…The IUGR foetus displays typical haemodynamic alterations, including redistribution of its cardiac output to preserve oxygen and nutrient supply to the brain (‘brain sparing') [6]. Our group has previously shown that this brain-sparing effect is postnatally sustained up to 72 h [5,7]. Nevertheless, normalisation - or a trend toward normalisation - of cerebral haemodynamic parameters throughout the first few days of life has also been observed, which could indicate that the cerebral circulatory adaptations following IUGR are transitory [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using the Microsoft Excel RAND function, we randomly selected SGA neonates without hsPDA and AGA neonates with/without hsPDA (birth weight 20th to 80th percentile) to serve as control subjects. We have previously shown that gender significantly influences cerebral oxygenation [5,7]. To avoid bias caused by different gender distributions within the groups, the selection of control subjects was performed within the same male-to-female ratio as present in our SGA-hsPDA group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations